2022
DOI: 10.1001/jamadermatol.2022.2360
|View full text |Cite
|
Sign up to set email alerts
|

Absolute and Relative Risk of New-Onset Psoriasis Associated With Tumor Necrosis Factor-α Inhibitor Treatment in Patients With Immune-Mediated Inflammatory Diseases

Abstract: ImportanceTumor necrosis factor-α inhibitor (TNFi)–associated psoriasis is a rare adverse event following TNFi treatment. Data on the risk of developing TNFi-associated psoriasis when treated with TNFi are sparse.ObjectiveTo investigate the associated risk between new-onset psoriasis and TNFi treatment compared with nonbiologic conventional treatment.Design, Setting, and ParticipantsUsing Danish national registries (1995-2018), this cohort study included patients with inflammatory bowel disease (IBD) and/or rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“… 19 , 20 TNF-α-induced non-pustular psoriasis had a higher risk of occurring than PPP, but PPP had a higher relative risk (HR 6.5, p<0.001). 22 In contrast to PPP occurring independently of TNF-α inhibitors, TNF-α-induced PPP was more common in men (HR 19.682) and younger patients (HR 14.318). 21 …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“… 19 , 20 TNF-α-induced non-pustular psoriasis had a higher risk of occurring than PPP, but PPP had a higher relative risk (HR 6.5, p<0.001). 22 In contrast to PPP occurring independently of TNF-α inhibitors, TNF-α-induced PPP was more common in men (HR 19.682) and younger patients (HR 14.318). 21 …”
Section: Resultsmentioning
confidence: 94%
“…Increased risk predominant in younger patients (HR 14.318, 95% CI 2.915–70.315). Infliximab but not adalimumab showed significant associations with risk of PPP: HR 9.504, 95% CI 2.767–32.648 High Thein D, 2022 22 Cohort study 3 TNF-α inhibitor 109,085 108,024 patients received conventional therapy and 20,910 received TNF-α inhibitor, 62% female, median age 50 (34–64) years with TNF-α inhibitor for IBD or RA 0.12% development of new PPP. TNF-α inhibitor-associated Pso: Non-pustular Pso is more prevalent but pustular Pso has the highest relative risk (HR of developing a pustular type of psoriasis 6.50 (95% CI, 4.60–9.23; P < 0.001)) High Kim M, 2021 23 Retrospective cohort study 3 Nail involvement 116 116 patients with PPP from Seoul University Hospital, 59.9% female, 14.7% had concomitant Pso and 8.6% had concomitant PsA, 66.3% had Involvement NAPSI is correlated with PPPASI (p=0.01) and involvement area (p=0.04); Crumbling was associated with higher PPPASI (p = 0.01) and onycholysis was associated with lower PPPASI (P = 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, biologics reduced the severity of symptoms in some patients and affected RA activity; however, determining which biologics resulted in less severe disease was difficult. Recently, Thein et al 15 reported hazard ratios (HRs) of 2.12 (95% CI: 1.87–2.40; P < 0.001) and 6.50 (95% CI: 4.60–9.23; P < 0.001) for developing non‐pustular and pustular psoriasis, respectively, compared with conventional treatment.…”
Section: Epidemiology Of Tnfi‐associated Psoriasismentioning
confidence: 99%
“…Existing approaches for AE surveillance may involve prospective registry studies, spontaneous postmarketing reporting (e.g., the Food and Drug Administration’s AE Reporting System [FAERS]) 1 , literature searches, and/or analyses of the structured data from claims and electronic health records databases 2,3 . These approaches have provided important data on the postmarket safety of medications but are limited by expense, small numbers, under/over-reporting 4,5 , missing data, limitations in inferring causality, and suboptimal sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%